Tathwiiru Wasaa`Ithi Lu'batid Domiino Litarqiyatil Mufradaatil Lughah Al-'Arabiyyah Wa Mahaaratil Kalaam Fi Al-Madrasah Ad-Diniyyah At-Ta'limiyyah Zainul Hasan Genggong. - Rachmawati, Devi Aprilia; Muhammad Sugianto; Ainur Rofiq Sofa (Tarling : Journal of Language Education, 2025)
This study aims to develop instructional media in the form of a domino card game to enhance vocabulary mastery and speaking skills on the topic of al-hayawan for second-grade students at Madrasah Diniyah Ta’limiyah Zainul Hasan Genggong. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed media was validated by material and media experts, resulting in an average score of 97.7% for content feasibility and 96.3% for media design, both categorized as "Highly Feasible." The media was implemented with 28 students, divided into small groups to play while practicing vocabulary and speaking in Arabic. The effectiveness test results showed an increase in the students' average scores from 55.8 in the pre-test to 73.3 in the post-test, with an N-Gain Score of 0.4, categorized as "Moderate." Additionally, the number of students who achieved scores above the Minimum Mastery Criteria (KKM) increased from 6 to 17. Both students and teachers responded very positively to this media, as the domino game made learning more interactive and enjoyable. Thus, the domino card game can be an innovative alternative in Arabic language learning, not only improving vocabulary comprehension but also training students' confidence in speaking.